Overview of Diabetic Nephropathy in Type 2 Diabetes Mellitus Patients at Royal Prima Hospital Medan Indonesia - Riski N. Situmeang; Erwin Sopacua (Archives of The Medicine and Case Reports, 2022)
Diabetes Mellitus (DM) is a chronic disease characterized by blood glucose (blood sugar) levels exceeding normal. Diabetic nephropathy is a chronic microvascular complication that often occurs in diabetics. This study presents a picture of diabetic nephropathy in type 2 DM patients at the Royal Prima Hospital in Medan. This research is a type of descriptive research. The sample from this study was the total data of patients suffering from diabetic nephropathy who met the inclusion and exclusion criteria at Royal Prima Hospital from January 1, 2020 – to December 31, 2020. The inclusion criteria for the subjects of this study were complete patient medical records, type 2 diabetes patients, urinalysis tests. (proteinuria ≥ +2), renal function examination exceeds normal values, blood urea, and creatinine. The mean age of diabetic nephropathy patients was 57.52 years and the majority were 62 men (50.8%). The average picture of urea levels in diabetic nephropathy patients is 51.8 and the average creatinine level is 1.48. The majority of patients with diabetic nephropathy do not have proteinuria. And the average blood sugar level is 267 mg/dL. In conclusion, the incidence of diabetic nephropathy is highest in patients aged 57 years. The mean value of urea level is 51.80 mg/dl, creatinine value is 1.48 mg/dl, and the average blood sugar level is 267 mg/dl. Most proteinuria was in the negative category of as many as 107 people (87%).